2022
DOI: 10.1186/s12885-022-09481-9
|View full text |Cite|
|
Sign up to set email alerts
|

Aberrant hydroxymethylation in promoter CpG regions of genes related to the cell cycle and apoptosis characterizes advanced chronic myeloid leukemia disease, poor imatinib respondents and poor survival

Abstract: Background There is strong evidence that disease progression, drug response and overall clinical outcomes of CML disease are not only decided by BCR/ABL1 oncoprotein but depend on accumulation of additional genetic and epigenetic aberrations. DNA hydroxymethylation is implicated in the development of variety of diseases. DNA hydroxymethylation in gene promoters plays important roles in disease progression, drug response and clinical outcome of various diseases. Therefore in this study, we aimed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 84 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…In this study, we associated DAPK1 overexpression and hypomethylation with therapeutic failure, and poorer survival in patients with normal karyotype. DAPK1 has also been associated with resistance to imatinib in chronic myeloid leukemia ( Guru et al, 2022 ), autophagia ( Singh et al, 2016 ), alterations in the p53 signaling pathway in chronic lymphocytic leukemia ( Wang et al, 2014 ) and methylated in myelodysplastic syndrome ( Greco et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we associated DAPK1 overexpression and hypomethylation with therapeutic failure, and poorer survival in patients with normal karyotype. DAPK1 has also been associated with resistance to imatinib in chronic myeloid leukemia ( Guru et al, 2022 ), autophagia ( Singh et al, 2016 ), alterations in the p53 signaling pathway in chronic lymphocytic leukemia ( Wang et al, 2014 ) and methylated in myelodysplastic syndrome ( Greco et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is no consensus on its prognostic role. DAPK1 has also been associated with resistance to imatinib in chronic myeloid leukemia (43), autophagia (74), alterations in the p53 signaling pathway in chronic lymphocytic leukemia (40) and methylated in myelodysplastic syndrome (38).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our research group has also revealed the correlation of SOX30 , ID4 and DLX4 hypermethylation with disease progression in CML [ 19 21 ]. A recent study demonstrated that promoter hydroxymethylation of tumor suppressor genes DAPK1 , RIZ1 , P16INK4A , RASSF1A and p14ARF ARF was a characteristic feature of CML disease progression and indicated poor imatinib response and poor overall survival of CML patients to imatinib therapy [ 22 ]. On the basis of our previous study [ 12 ], we further investigated SLIT2 promoter methylation in another myeloid malignancy CML.…”
Section: Discussionmentioning
confidence: 99%